2016
DOI: 10.3847/0004-637x/829/2/74
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space Telescope Constraints on the Winds and Astrospheres of Red Giant Stars*

Abstract: We report on an ultraviolet spectroscopic survey of red giants observed by the Hubble Space Telescope, focusing on spectra of the Mg II h & k lines near 2800Å in order to study stellar chromospheric emission, winds, and astrospheric absorption. We focus on spectral types between K2 III and M5 III, a spectral type range with stars that are noncoronal, but possessing strong, chromospheric winds. We find a very tight relation between Mg II surface flux and photospheric temperature, supporting the notion that all … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Wind velocities are generally found to decrease with spectral type, from ∼40 km s −1 at K1.5 III to ∼20 km s −1 at M5 III. The power law index in the Wood et al (2016) empirical relation F M gII ∼ T 9.1 ef f is remarkably close to the index of a theoretical relation de-rived by Bohn (1984) linking the flux of acoustic power F acoustic and the effective temperature: F acoustic ∼ T 9.75 ef f . This makes it highly likely that the basal flux is indeed related to acoustic power, rather than magnetic effects (we thank the anonymous referee for pointing this out to us).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Wind velocities are generally found to decrease with spectral type, from ∼40 km s −1 at K1.5 III to ∼20 km s −1 at M5 III. The power law index in the Wood et al (2016) empirical relation F M gII ∼ T 9.1 ef f is remarkably close to the index of a theoretical relation de-rived by Bohn (1984) linking the flux of acoustic power F acoustic and the effective temperature: F acoustic ∼ T 9.75 ef f . This makes it highly likely that the basal flux is indeed related to acoustic power, rather than magnetic effects (we thank the anonymous referee for pointing this out to us).…”
Section: Discussionsupporting
confidence: 84%
“…They further reported that their non-detection of a magnetic field on the post-RSG star ρ Cas suggests that the magnetic field disappears, or at least becomes undetectable with present methods, at later evolutionary stages and that their analysis of α 1 Her supports the proposed reclassification of the star as an M-type asymptotic giant branch star. Wood et al (2016) discuss constraints on the winds and astrospheres of Red Giant Stars provided by HST observations, focussing on spectra of the Mg II h and k lines near 2800Å. They studied stellar chromospheric emission, winds, and astrospheric absorption, concentrating on spectral types between K1.5 III and M5 III (noncoronal stars that possess strong, chromospheric winds).…”
Section: Discussionmentioning
confidence: 99%
“…In the red giant phase alone, the solar wind will likely be cooler (. 10 4 K), with lower velocities, but higher densities, leading to mass-loss rate that will be several magnitudes higher than today (Wood et al 2016). Solar rotation will change considerably due to its radius expansion.…”
Section: Final Remarks and Open Questionsmentioning
confidence: 96%
“…However, emission could be higher by about one order of magnitude (see their Fig. 2, as well as Wood et al 2016). We relied on these studies to estimate the effect of the Mg ii lines on photometry.…”
Section: Line Emissionmentioning
confidence: 99%